Paediatric Orthopaedics in Clinical Practice - Aresti, Nick A.; Ramachandran, Manoj; Paterson, Mark (J.M.H.); Barry, Matthew (In Clinical Practice, 2016)
This book provides orthopaedic surgeons in training with concise and relevant core knowledge on all aspects of children's orthopaedics. Content includes the common orthopaedic conditions that affect children, and key management points in each chapter are highlighted for readers to quickly access this information. The aim of this resource is to offer an authoritative guide on all facets of children's orthopaedics so the treating doctor has enough information to confidently allay the anxieties of the patient and their parents, and to identify when to refer the child to a paediatric orthopaedic surgeon. This book will be an essential reference guide for newly qualified orthopaedic specialists, as well as paediatricians and family doctors working in busy clinics that treat children who present with orthopaedic conditions.